Analisis Efektivitas Pastoral Hukum Perkawinan Gereja Katolik terhadap Prosesi Nikah Adat Suku Dayak Banyadu Kalimantan Barat - Alnija, Marianus Dinata; Jewarut, Siprianus; Lektawan, Fedrianus K.; Gadur, Fransiskus Heryman Surya (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study aims to analyze the effectiveness of the Catholic Church's pastoral care for marriage in traditional marriages of the Dayak Banyadu people in Banyuke Hulu, West Kalimantan. The study was conducted using a mixed methods research method with a sequential explanatory design. The results showed that the level of respondents' understanding of the Dayak Banyadu traditional marriage procession and Church marriage law reached a very good percentage (80.00%), indicating adequate understanding among traditional leaders. However, the evaluation of the effectiveness of the Catholic Church's legal care for marriage still showed less than optimal results. This finding was reinforced by the results of interviews with three key informants who consistently stated that the care had not been effective. Field observations confirmed that the process of integrating Catholic Church marriage law into the Dayak Banyadu traditional marriage procession had been implemented.